Randomized placebo‐controlled trial of intravenous immunoglobulin in autoimmune LGI1/CASPR2 epilepsy - Dubey, D; Britton, J; McKeon, A; Ramberger, M; Waters, P; Irani, S (Wiley, 2019)
Objective Drug‐resistant seizures are common in patients with leucine‐rich, glioma‐inactivated 1 (LGI1)‐IgG associated and contactin‐associated protein‐like 2 (CASPR2)‐IgG associated encephalitis. We performed the first randomized double‐blind placebo‐controlled trial to evaluate efficacy of intravenous immunoglobulin (IVIG) in reducing seizure frequency.